2017
DOI: 10.1186/s12879-017-2679-z
|View full text |Cite|
|
Sign up to set email alerts
|

Accuracy and reliability of an NS1 rapid immunochromatographic test for DENV-1 diagnosis at point of care and in the laboratory

Abstract: BackgroundRapid immunochromatographic tests (ICT) for dengue non-structural protein 1 (NS1) have shown good performance for diagnosing acute-phase dengue in serum in laboratory settings, but rarely have been assessed in whole blood and at point of care (POC). This study compare the accuracy and inter- and intra-observer reliability of the NS1 Bioeasy™ ICT in whole blood at POC versus serum in the laboratory, during a DENV-1 epidemic.MethodsCross-sectional study involving 144 adults spontaneously demanding care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Most published dengue RDT evaluation studies used serum samples. Some studies also used whole blood specimen and only one used capillary blood [26][27][28][29]. The excellent agreement between the results tested on capillary, venous, and serum samples in this study demonstrated that all three of them can be used on RDT, provided that anticoagulant-coated tool is used for the collection of whole blood specimen.…”
Section: Discussionsupporting
confidence: 52%
“…Most published dengue RDT evaluation studies used serum samples. Some studies also used whole blood specimen and only one used capillary blood [26][27][28][29]. The excellent agreement between the results tested on capillary, venous, and serum samples in this study demonstrated that all three of them can be used on RDT, provided that anticoagulant-coated tool is used for the collection of whole blood specimen.…”
Section: Discussionsupporting
confidence: 52%
“…After removing duplicates, we reviewed 3,783 abstracts, and selected 108 articles for reading the full-texts, of which 57 were selected for this review (Figure 1). The studies assessed multiple ICT brand tests with different analytes: five assessed IgA 24,25,26,27,28 , 21 NS1 10,27,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47 , 12 IgM/IgG 27,34,48,49,50,51,52,53,54,55,56,57 , and 25 NS1/IgM/IgG 29,36,37,40,46,58,59,60,61,62,63,…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…According to the assessment of methodological quality conducted with the QUADAS 2 tool, of the 57 included studies, only six 29,30,38,39,69,78 did not show risk of bias, and 25 (43.8%) of the them showed high risk of bias regarding the patient selection process (Figure 2), mainly due to case-control design. Ten of them showed high risk of bias concerning flow and timing, mainly for excluding patients from analysis or for adopting inappropriate intervals between index and reference tests.…”
Section: Quality Assessment Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies show high variability in the sensitivity, specificity, and predictive values due to factors like patient population enrolled, differences in the DENV serotypes, timing of sample collection, and the test or tests considered as reference standards. However, these studies shed light on the usefulness of these approaches for dengue case confirmation and establish their potential as predictors of the disease severity [34,[61][62][63][64][65][66][67][68][69].…”
Section: Introductionmentioning
confidence: 99%